Personal Character Education Values in Andrea Hirata’s Ayah “The Father” - Nurdin Nurdin; Mohammad Harun; Ramli Ramli (Center of Language and Cultural Studies, 2020)
This research was aimed at describing personal values of character education in Ayah written by Andrea Hirata, a best-seller novel published by PT Bentang Pustaka in 2015. The novel is 396 pages long, divided into 69 chapters. This research is qualitative research with a documentation study design. The data for this research consists of parts of the novel where personal values were found. The data were analyzed using descriptive analysis by describing the data, pointing out the personal values, and explaining it in detail, discussing the research results, and drawing conclusions. The research results show that the personal values found in the novel Ayah include honesty, accountability, self-confidence, hard work, independence, love of knowledge, entrepreneurship, and a healthy lifestyle. The values of love of knowledge and hard work are more dominant, which indicates that the author respects those values.